Definition of acoustic-emission characteristics of aircraft with THE uSE OF parametric registerING DEVICES on SUPERHIGH FREQUENCES and opticAL BEAMS - V. D. Roubtsov; S. A. Dubyanskiy (Научный вестник МГТУ ГА)
This article describes the method of definition of acoustic-emission characteristics of aircraft with the use of parametric registering devices on superhigh frequencies and optical beams. The results of the research of acoustic response and bandwidth of registering devices when using those beams are given.